Criminalistic recommendations of carrying out interrogation (Journal of actual problems of jurisprudence, 2018)
In article tactical recommendations about carrying out interrogation are formulated. Each council of criminalists is approved by investigative practice and authors opened in brief the maintenance of everyone. The indication interrogated are under construction on perception of information and are shown what its psychophysiological bases in article. As psychological contact, statement of the correct questions, the critical analysis of the indication and other councils is important, according to authors are presented in article.Key words: Interrogation, proof, tactics, policy strokes, criminalistic recommendation, perception, storing, reproduction, psychological contact, question, analysis.